Leptoecia midatlantica, a new species of the deep-sea quill-worms (Polychaeta: Onuphidae: Hyalinoeciinae) from the Mid-Atlantic Ridge - Budaeva, Nataliya (Zootaxa, 2012)
A new species of the genus Leptoecia Chamberlin, 1919, collected from the northern part of the Mid-Atlantic ridge at depths around 2100–2700 m, is described. Leptoecia midatlantica sp. nov., is characterized by the presence of both uni- and bidentate simple falcigers on the first pair of parapodia, presence of dorsal cirri on all chaetigers, dorsoventrally flattened organic tube, and appearance of the first subacicular hooks around chaetiger 28–39. The unusually high intraspecific variability of several morphological characters (dentition of falcigers, shape of prostomium, and number of anal cirri) in the examined material is described. A key for the seven known species of the genus Leptoecia is provided.